2019
DOI: 10.1016/j.ygyno.2019.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific HPV type distribution in high-grade cervical disease in screened and unvaccinated women

Abstract: • HPV distribution was markedly polarised by age in women referred to colposcopy. • HPV16/18 was twice as common in women b30 years than in women ≥45 with HSIL lesions. • In women ≥45 years other high-risk HPVs were more common in HSIL lesions. • In women ≥45 years approximately 10% of HSIL lesions were negative for high-risk HPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
58
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 37 publications
11
58
2
1
Order By: Relevance
“…Growing evidence suggest how various HPV types might have a different impact on the basis of age [ 11 12 13 ]. Aro et al, [ 14 ] evaluated HPV types distribution among a cohort of 1,279 women with cervical dysplasia [ 11 ]. The authors observed that HPV type distribution was distinctly polarized by age with HPV16/18 being markedly HPV16/18-related lesions more prevalent young women.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggest how various HPV types might have a different impact on the basis of age [ 11 12 13 ]. Aro et al, [ 14 ] evaluated HPV types distribution among a cohort of 1,279 women with cervical dysplasia [ 11 ]. The authors observed that HPV type distribution was distinctly polarized by age with HPV16/18 being markedly HPV16/18-related lesions more prevalent young women.…”
Section: Discussionmentioning
confidence: 99%
“…The morbidity and mortality of cervical cancer incidence in developed countries has fallen over the last two decades because of an enhanced awareness of cervical cancer prevention and effective screening [5]. However, infection rate of HPV has uctuated and not shown a downward trend, indicating a relatively heavy burden of HPV infection in China [6,7]. HPV genotypes are linked to the degree of cervical lesions [6].…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, high-risk HPV (HR-HPV) type cause cervical, anal, and other genital cancers, which could be detected in 99% of cervical cancers-the second most common cancer in women worldwide. HPV16 and -18 have been found to be the most pathogenic of the HR-HPV types, causing about 70% of cervical cancers worldwide [7][8][9][10]. Of note, most HPV infections are completely asymptomatic, resulting in a delay in diagnosis and follow-up treatment with disastrous consequences [11].…”
Section: Introductionmentioning
confidence: 99%
“…The morbidity and mortality of cervical cancer incidence in developed countries has fallen over the last two decades because of an enhanced awareness of cervical cancer prevention and effective screening [5]. However, infection rate of HPV has fluctuated and not shown a downward trend, indicating a relatively heavy burden of HPV infection in China [6,7]. HPV genotypes are linked to the degree of cervical lesions [6].…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, high-risk HPV (HR-HPV) type cause cervical, anal, and other genital cancers, which could be detected in 99% of cervical cancers-the second most common cancer in women worldwide. Especially, HPV16 and − 18 have been found to be the most pathogenic of the HR-HPV types, causing about 70% of cervical cancers worldwide [7][8][9][10]. Of note, most HPV infections are completely asymptomatic, resulting in a delay in diagnosis and follow-up treatment with disastrous consequences [11].…”
Section: Introductionmentioning
confidence: 99%